Design of Elemental Nanoparticles and their Application in Catalysis, Lithography and Biochemistry - Fasciani, Chiara (Université d'Ottawa / University of Ottawa, 2014)
The interest in metal nanoparticles has seen an exponential growth in the last twenty years, due to the astonishing properties these materials possess on the nanometer size scale. Compared to the bulk metal, nanoparticles present different optical and physical properties, which can be tuned according to their size or shape. As an example, colloidal solutions of 15 nm gold nanoparticles appear red, a very different tint as compare to the typical gold color of a gold brick. The reason for this variation is due to the fact that visible light wavelengths are bigger than the nanoparticles sizes. Therefore, after excitation, part of the light is absorbed and produces a coherent oscillation of the surface electrons, resulting in a phenomenon known as surface plasmon resonance. At this point the system tends to return to the initial state, following different pathways. One of the processes occurring is the local release of heat around the nanoparticle surface. The aim of this thesis is to gain more insight into the actual temperature values achievable after plasmon irradiation and to explore the possible applications of the localized heat release. Synthetic procedures developed in the Scaiano group were used to synthesize and modify the nanoparticles. The applicability of these photochemical procedures was extended to the synthesis of bimetallic silver-gold (Ag/Au) core-shell materials via a controlled and facile synthesis method. Ag/Au core-shells combine the optical and physical properties of gold and silver together and they have shown promise as potential antimicrobial agents. Information regarding the temperatures achievable after plasmon excitation has been obtained using dicumyl peroxide as a molecular thermometer and has indicated temperatures close to 500oC near the nanoparticle surface. This finding was a precious guideline for the selection of thermal processes that can be performed after plasmon excitation. The catalytic reduction of resazurin to resorufin was one of the reactions chosen. This process, indeed, appears significantly faster (nanoseconds) when performed using AuNP irradiated at 530 nm. The use of laser and LED irradiations has been a constant throughout this work with both systems being to suite the experimental needs. The high temperature reached irradiating metal nanoparticles has also been used to trigger the caprolactam polymerization, in such a way that only in the light exposed position AgNP favored nylon formation, presenting promising applications in lithography. Moreover, DNA melting processes have been successfully studied, by employing a switch On/Off controllable irradiation of AuNP, aiming for eventual application in the polymerase chain reaction (PCR) process. Finally, considerable work has been done in the functionalization and modification of carbon-based materials. Functionalization with silver and gold nanoparticles has been performed using a photochemical procedure, during which a different behavior was observed for the two metals. In addition, modification of the reduced graphene oxide morphology was obtained by laser irradiation without the use of any external template. The spherical reduced graphene oxide, thus obtained, has shown promising potential in water splitting catalysis. In this system, the evolution of hydrogen was observed by employing only spherical reduced graphene oxide and visible light (532 nm laser or LED irradiation). In summary, this thesis describes how light can not only be used to synthesize and modify nanomaterials, but also to perform high energetic processes at room temperature, taking advantage of the nanoscale properties of the materials being used.
Keywords: Nanoparticles; Plasmon